CHALLENGES OF AL-FARĀ’IḌ APPLICATION IN A MULTI-RELIGIOUS SOCIETY: THE CASE OF YORUBA MUSLIMS OF LAGOS AND OYO STATES, SOUTHWESTERN NIGERIA - Busari, Jamiu Muhammad; Ashafa, Saheed Afolabi; Busari, Saheed Abdullahi (Jurnal Syariah, 2024)
Yoruba Muslims of Southwestern Nigeria are among the foremost West Africans who had the earliest contact with Islam before the advent of British colonization in the 1850s. By 1775 C.E, Islam had been firmly entrenched in the nooks and crannies of Yorubaland, Southwest Nigeria, where Mosques and Madāris (Islamic Schools) were established to preach and teach the religion. However, with the British intrusion and amalgamation of the then Southern and Northern Protectorates to form a country called Nigeria, the colonialists had submerged all existing legal systems, whether customary or religious, under the control of English common law; hence, the application of Islamic law (Sharī‘ah) became a herculean task. To this end, with the dichotomy syndrome in Islamic law application between Northern and Southern Nigeria, Yoruba Muslims have been battling the non-statutory recognition of Sharī‘ah for over a century with no solution in sight. This, without mincing words, has deeply affected the application of the Islamic law of inheritance (al-farā’iḍ) on deceased’s estates as enshrined under Islamic law. Therefore, this present paper, through an analytical method, examines the challenges facing Yoruba Muslims in Lagos and Oyo States, Southwest Nigeria, in utilizing Islamic law of inheritance on deceased’s properties amidst the enforcement of the Nigerian legal system, the Yoruba customary law and States’ Administration of Estate Laws. It also enunciates the judicial prospects as being utilized by Muslims in the absence of statutory Islamic courts through the Independent Sharī‘ah Panels. The paper discovered that the challenges of al-farā’iḍ application might not be overturned in the near future until Yoruba Muslims reinvigorate their agitations for constitutional review to enforce statutory Sharī‘ah recognition and application in all matters that concern Muslims within the purview of the Nigerian legal system.